PHRASEOLOGICAL WORLDVIEW - Atabaeva Gozzal Bazarbaevna (Western European Studies, 2024)
The article talks about one of the new directions of linguistics - linguoculturalism and the linguistic and cultural features of phraseological units. Researches of scientists on the linguistic picture of the world and opinions about the special place of phraseological units in the linguistic picture of the world are given. The national-cultural features of phraseological units in the linguistic picture of the world were discussed on the example of phraseological units with numbers in the Karakalpak language
Keywords: Linguoculturology; worldview; connotation